FOSSIL ELASMOBRANCHS AND STRATIGRAPHY OF CRETACEOUS DEPOSITS, KANIV - Popova, L.; Ogienko, O.; Sokolskiy, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
A study into the sections of the Cretaceous deposits at the Southern Kaniv dislocation revealed teeth of fossil Elasmobranchs in thin quartzglauconitic gravel interlayers. The species composition of the fauna is associated with the Albian-Cenomanian (for a single gravelly interlayer of Kholodniy Yar taphocoenoses) and the Cenomanian (two fossiliferous gravelly interlayers at Melanchin Potik). Along with elasmobranchs, fossiliferous gravel sands contain remains obviously redeposited from the more ancient strata. The probability and scope of redeposition decrease from the Kholodnyi Yar taphocoenosis, through the Melanchin Potik lower layer, to the Melanchin Potik upper layer. The stratigraphic intervals are assumed to be wider for Kholodnyi Yar (the Albian-Cenomanian) and narrower for Melanchin Potik (the Cenomanian). The fossiliferous gravelly interlayers resulted from transgressive-regressive events. With the transgressing sea eroding the previously formed deposits containing fauna and flora remains, the latter were redeposited, sorted and waterworn due to the tidal zone hydrodynamics. The conditions described account for mixed taphcaenoses (those of the Melanchin Potik lower layer and Kholodnyi Yar). Besides, a more powerful rewashing may have affected a previously gravelly interlayer, which is likely for Kholodnyi Yar. The transgressive events seem to have been rather dynamic: deep-water deposits containing no fossils rapidly replaced the litoral and sublitoral ones. The following regressive-transgressive cycle therefore resulted in the formation of unmixed taphocoenoses in the basal horizon. In general, the Cenomanian palaeolandscapes of the study area were more even than the Albian ones. The Albian islands were characterized by a great variety of mesophite flora and physiographic conditions. On the contrary, low flattened shores of the Cenomanian islands did not favour the development of tree vegetation.